Implementasi Permainan Pemadam Kebakaran Menggunakan Teknologi Virtual Reality - Nur Muhammad Rashid; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fire is a disaster that often occurs in the community but there are still many lay people who do not know how to use and the types of fire extinguishers or APAR. According to interviews with the head of the Technical Implementation Unit of Fire Brigade, in the training and the introduction of the Fire Fighter Department and Regional Disaster Management Agency (BPBD) there are shortcomings such as the number of APAR that amounts to a little, so employees can not try. APAR training also has an accident risk. Therefore, case studies in this study are the general public who do not understand about the type of APAR and its usefulness. Based on the problems described, this research will design and build a simulation and game using Virtual Reality technology. By utilizing this technology the user is not required to deal with real fire. This simulation can minimize accidents during APAR training and save the use of APAR. This simulation can visualize events so that the user can still feel how to extinguish the fire and the use of light extinguishers or APAR. With this simulation users will be better prepared when the fire occurred in the environment. Then for testing the usability of the implementation in building the Simulation and Fire Extinguisher game is obtained satisfactory results with an average above the standard that is 80.